PENGARUH KEPUASAN HIDUP DAN MODAL SOSIAL DIMEDIASI ORGANIZATIONAL CITIZENSHIP BEHAVIOR TERHADAP KINERJA TUGAS KEPALA SEKOLAH DASAR NEGERI DI KABUPATEN BATANG - Akhmad Fandi Susanto, 1352020004 (Jurnal Mahasiswa Pasca Sarjana, 2015)
This study aimed to determine and analyze the effect of life satisfaction and social capital mediated organizational citizenship behavior on the performance task research population is the Head of State Elementary School in Batang by taking the entire data population of 441. Mechanical test data using validity, reliability, classical assumption test, regression analysis and test mediation. The results showed that the variable life satisfaction is not proven effect on the performance of a task, while social capital has an influence on the performance of tasks. In addition, this study also shows that social capital is owned by someone would be more effective influence on the performance of his duties when mediated organizational citizenship behavior.. Key word : life satisfaction, social capital, organizational citizenship behavior and task performance.